Suitability of large-scale tree plantation models in Africa, Asia and Latin America for forest landscape restoration objectives - Péroches, A.; Baral, H.; Chesnes, M.; López Sampson, A.; Lescuyer, G. (Centre de coopération internationale en recherche agronomique pour le développement, 2022)
Today, tree plantations play a crucial role in supplying wood and wood-based products. They supply almost half of global demand, as well as supporting a diversity of ecosystem services. In tropical and subtropical areas, where tree growth is optimum and large tracts of land are available, forest restoration is presented as one of the most effective strategies for climate change mitigation. For these reasons, large-scale tree plantations are being encouraged in Africa, Asia and Latin America. Based on a review of the literature and of public databases on forest plantations, we drew up a typology of large-scale tree plantations in Latin America, Africa and Asia using four criteria: the management objective (production versus protection), number of species planted (multi-species versus mono-species), origin of species (exotic versus indigenous) and management status (industrial companies, private smallholders, state). Our analysis identified seven main plantation types and reveals that the two most common types represent almost 60% of the total planted area: (1) private mono-species plantations using exotic species; and (2) public production-oriented mono/multi-species plantations of indigenous trees. Numerous experimental studies were conducted in the 1950s and 1960s with a wide range of tree plantation models. However, few were adopted by operators because the production rates and financial returns were considered low. The dominant tree plantation types are failing to meet most of the forest restoration objectives set out in the Bonn Challenge (i.e., productivity, carbon storage, biodiversity conservation, rural livelihoods). Alternative large-scale tree plantation models could be promoted by focusing on the other goods and services that plantations can provide. This could be achieved if more diverse stakeholders were involved in plantation design and management processes, and if appropriate technical, financial, and institutional incentives were developed.